Sparking a Reading Revolution: Results of Early Literacy Interventions in Egypt and Jordan. Issue 155 (March 2017) - Gove, Amber; Brombacher, Aarnout; Ward‐Brent, Michelle
Abstract: This article examines the effects of two early grade reading interventions in two Arabic‐speaking contexts (Egypt and Jordan), developed in partnership with ministries of education. The interventions relied on similar research bases for improving reading instruction in Arabic. In Egypt, the results of a 166‐school pilot led to the national scale‐up of the Early Grade Reading Program for more than 4 million children in grades 1‒3. Informed by Egypt's experience, a demonstration effort in 43 schools led to a national rollout in Jordan's 2, 651 public primary schools and the creation of a remediation program. We reflect on the conditions that influenced the pilot and scale‐up outcomes given the commitments made to "inclusive and equitable quality education and lifelong learning opportunities for all" under the United Nations Sustainable Development Goals.